Revealing "Mafia Inc."? Financial crisis, organized crime, and the birth of new enterprises - Marco Le Moglie; Giuseppe Sorrenti (University of Zurich, Department of Economics, 2019)
We study the investment of organized crime in the legal economy. By using the shock induced on the Italian credit market by the 2007 subprime mortgage crisis, we document how provinces with a high organized crime presence have been impacted less by the crisis in terms of the establishment of new enterprises than provinces with a lower criminal infiltration. We provide evidence that the lower impact of the crisis is consistent with the presence of investments by organized crime in the legal economy. We corroborate this interpretation by comparing our results with the characterization made by the judicial authority of such investments and ruling out possible alternative explanations.
Keywords: K42; L26; 330; Mafia; organized crime; established enterprises; crisis